Application Of The Reading Aloud Method To Improve The Ability To Read The Quran in Islamic Education Learning at SD Negeri 054895 Batu Jong-Jong - Rahimi; Nurhefti; Hawa, Siti; Ariani, Fatimah; Ferawati, Dian (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to determine the application of the reading aloud method in improving the ability to read the Qur'an, especially in Surah Al-Alaq, in grade III students of SDN 054895 Batu Jong-Jong, Bahorok District, in the 2024/2025 academic year. The reading aloud method is one of the effective strategies in helping students learn to read the Qur'an correctly, as well as improve pronunciation and tajwid. This study uses a qualitative approach with the type of classroom action research (CAR). Data were obtained through observation, interviews, and reading tests of Surah Al-Alaq, which were then analyzed descriptively. The results of the study showed that the application of the reading aloud method can improve students' ability to read the Qur'an more fluently, smoothly, and in accordance with the rules of tajwid. In addition, students also showed an increase in self-confidence and skills in reciting the Qur'an reading in front of the class. Based on these findings, it is recommended that the reading aloud method be used routinely in the learning process of Islamic Religious Education, especially in learning to read the Qur'an, to improve the quality of Islamic religious learning in elementary schools.